Physical nature of abrasive wearproofness technically clean metals - Дворук, В.І.; Кіндрачук, М.В. (Problems of Tribology, 2014)
The results of theoretical-experimental research of tribotechnscal and reological properties are presented technically clean metals, directed on deepening and further development of rheology-kinetic pictures of nature of abrasive wearproofness. Correlative connection is set between wearproofness and reological parameter of metals, which submits to periodic conformity to law. The new model criterion of estimation of influence of adghesion co-operation of metals is offered on their wearproofness.